HALAL INDUSTRY DEVELOPMENT IN INDONESIA-MALAYSIA-THAILAND GROWTH TRIANGLE (IMT-GT): AN ANALYSIS OF ISLAMIC DIPLOMACY IN ENHACING REGIONAL COOPERATION AND ECONOMIC DEVELOPMENT - Candra , Rudi; Maulida, Savira; Anjani, Rara Sativa (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This research will discuss the growth of the halal industry in the Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) region, with an emphasis on boosting regional collaboration and economic development through Islamic diplomacy analysis. This research employs a qualitative approach, using data sources drawn from document analysis and literature reviews. Results from this research indicate that the growth of the halal industry in IMT-GT is critical to increasing regional collaboration and economic development. The analysis of Islamic diplomacy conducted in this study reveals that the development of the halal industry in IMT-GT adheres to diplomatic principles consistent with Islamic values, such as equality, equity, and justice in relations between countries or actors, and seeks to minimize conflict. Cooperation between Indonesia, Malaysia and Thailand in the halal tourism sector is increasingly optimal through increasing the development of the Islamic Tourism Center (ITC), implementing SISPARNAS as a service for tourism stakeholders, as well as international cooperation with the Growth Triangle concept which has succeeded in increasing cooperation in the field of Muslim Friendly Tourism. tourism strategy, cultural diplomacy, and digital diplomacy. This initiative aims to increase the competitiveness of halal products and services in the global market, strengthen regional cooperation in developing the halal industry, especially in the ASEAN region, and aims to strengthen Muslim solidarity to promote a positive image of Islam in the international World.